Unlocking the Potential: Evaluating the Impact of Padlet in Online-Based Learning - Beni Surya Purba; Gamar Al Haddar; Deki Zulkarnain; Maulana Erwin Syahputra (Institute of Computer Science (IOCS), 2024)
Online education has become an integral part of modern education, with the rapid advancement of technology shaping the way students access and engage with learning content. In this evolving landscape, digital tools play a pivotal role in enhancing the online learning experience. This re-search investigates the effectiveness of the Padlet application in online-based learning, aiming to shed light on its impact on student engagement, collaboration, and learning outcomes. The study employs a mixed-methods approach, combining quantitative analysis of pre- and post-assessment scores and survey data with qualitative insights from interviews, focus group discussions, and content analysis of Padlet boards. Participants include students, educators, and administrators from diverse online-based learning environments. The quantitative analysis re-veals a statistically significant improvement in learning outcomes among students who utilized Padlet, indicating its positive influence on academic achievement. Survey data and qualitative analysis underscore Padlet's role in facilitating interactive and collaborative learning experiences, fostering critical thinking, creativity, and peer-to-peer knowledge sharing. This study provides valuable insights into the potential of Padlet as a versatile tool that can significantly enrich online-based learning experiences. The adaptability and user-friendliness of Padlet make it a valuable resource for educators and students alike.